Crescimento, consumo alimentar e qualidade da dieta de crianças menores de dois anos nascidas de mães infectadas pelo HIV - Almeida, Daniela Neri Gama de [UNIFESP] (2016)
Introduction: HIV-exposed, uninfected (HEU) infants are potentially at risk for non-communicable diseases due to in utero exposures. Feeding practices of the infant could compound this risk. Moreover, excessive added sugars intake and ultraprocessed product (UPP) consumption increase the risk of obesity and chronic diseases. However, few studies have evaluated dietary intake of HEU children. In a sample of HEU infants/toddlers followed at the University of Miami HIV Screening Program we determined: i) dietary factors associated with rapid weight gain (RWG) from birth to 6 months; and ii) the proportion of infants/toddlers age 6-19 months who consumed added sugars in excess, and the contributions of each food group to total energy and to energy from added sugars. Methods: two manuscripts were produced based on data obtained originally from a longitudinal assessment on growth and dietary intake of HEU infants: i) in a cross-sectional analysis, logistic regression was used to determine dietary factors associated with RWG defined as a greater than 0.67 SD change in weight-for-age Z-score from birth to assessment; ii) in another cross-sectional analysis, food items consumed (n = 286) by HEU infant/toddlers from 6-19 months were converted into energy and classified into one of the four groups of the NOVA System according to degree of industrial processing. Results: A total of 86 full-term HEU infants mean age of 3.4 ± 1.8 months were included in the first analysis. Overall, 39.5% of infants exhibited RWG. A significant association between consumption of infant cereal and RWG (OR, 3.52; 95% CI, 1.02?12.10) was found after adjusting for birth weight, current age, and energy intake. Those infants who consumed the highest tertile of protein were less likely to gain weight rapidly after adjusting for the same covariates (OR, 0.15; 95% CI, 0.02?0.94). In the second analysis, forty-eight HEU infant/toddlers, median age 12.3 months [IQR: 11.85-13.69 months], were studied. Forty percent of children were overweight. Fifty percent of the sample consumed a high added sugar diet. UPP comprised 65% of energy intake and 100% of the energy intake from added sugars. Infants/toddlers with high added sugar intake consumed more calories from UPP (760 vs. 530 kcal, P=0.006) and less calories from fresh foods (90 vs. 413 kcal, P=0.006) than those with adequate intake. No differences in overweight rate were found between the groups. Conclusions: Overall differences in weight gain during early infancy are at least partly explained by means of infant feeding in young HEU infants in the United States. Excess added dietary sugar, with more than half of total dietary energy from UPP, are common dietary constituents among HEU, and these rates are comparable to the general US population (60%). UPP contributes to the entire amount of added sugars consumed by this young population. Actions that encourage the introduction of complementary foods based on minimally processed foods and discourage consumption of AUP are essential.